THE THEORETICAL AND METHODOLOGICAL BASES OF THE ISSUES OF AGRARIAN AND MARKET POLICY OF UZBEKISTAN IN 1996-2000 - Hamroyev Dilmurod (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides a theoretical study of agrarian and market policy in Uzbekistan in 1996-2000. The article analyzes agrarian and market policy on a conceptual basis.